Epidemiology and Molecular Confirmation of E. coli Isolated from Diseased Fish in Muzaffargarh, Punjab, Pakistan - Hassan, Ahmad; Ali, Shahzad (BioScientific Review, 2024)
Background Fish is an important source of protein and vitamins, such as vitamin D and B2 (riboflavin) for human beings. However, they are plagued with a variety of disease-causing pathogens, resulting in significant economic losses. Among these pathogens, Escherichia (E.) coli are prominent, worldwide. This study aimed to conduct epidemiological surveillance and identification of E. coli strains isolated from diseased fish in District Muzaffargarh, Punjab, Pakistan. Methodology A total of fifty (50) diseased fish samples were collected from various fish farms in the district. The isolation process involved enriching the samples in nutrient broth and incubating them at 37°C for 24 hours. After enrichment, the samples were inoculated on MacConkey agar and incubated again at 37°C for 24 hours. Following incubation, Gram staining was performed to identify E. coli and confirm its presence. These isolates were subjected to PCR using the uspA gene for confirmation. Results Among fish diseases, Hemorrhagic septicemia was reported to have the highest prevalence (22%), while 12% of fish samples were infected with abdominal dropsy and fin rot. In total, six (06) E. coli isolates were obtained from five different diseased fish samples and confirmed by PCR-based detection of uspA gene. Conclusion The current study found a link between disease-affected fish and naturally occurring E. coli, with molecular confirmation using the uspA gene. Effective management of soil, stock, water, nutrition, and environment is crucial to control losses caused by E. coli as opportunistic fish pathogens and spoilage agents.